Evaluation of the confidence and competency of house officers in rapid sequence intubation (ECCHO-RSI) in Emergency Department of Hospital Canselor Tuanku Muhriz, Universiti Kebangsaan Malaysia Medical Centre during COVID-19 pandemic - Wong, Kevin Chuing Shen; Ahmad Khaldun Ismail; Siti Sarah Md Zhahir; Ida Zarina Zaini (Penerbit Universiti Kebangsaan Malaysia, 2021)
Rapid sequence intubation (RSI) is a procedural skill that house officers (HO) in Malaysia need to learn during their training in emergency department (ED) posting. This study aimed to evaluate the confidence and competency of HO in RSI after completed training in the ED of a university hospital during the COVID-19 pandemic. A prospective cross-sectional study was conducted among 44 HO. When they begin their posting in ED, a pre-test was done with a questionnaire to evaluate their knowledge and confidence level. A post-test was conducted three months later with a similar questionnaire. They underwent an objective structured clinical examination to evaluate their skill. A feedback survey form was filled in by the HO regarding their satisfaction in training in emergency rotation. The mean score for pre-test and post-test were 8.75 ± 3.005 and 14.86 ± 2.258, respectively (P = 0.000). There was an improvement in knowledge level and confidence level between pre-test and post-test (all P = 0.000). 43.2% were competent in knowledge, while 65.9% were competent in skill. 35 house officers filled in the feedback survey form. It showed that 42.9% (n = 15) were very satisfied and 28.6% (n = 10) were satisfied with the training in ED. There was an improvement in knowledge and confidence level in RSI among the HO after ED rotation. The clinical exposure in intubating real patients was limited among HO due to the COVID-19 pandemic. The training of HO for RSI in ED needs to be further improvised to optimize their learning process.